Dr. Seuss' the Lorax - Renaud, Chris; DeVito, Danny; Helms, Ed; Efron, Zac; Powell, John, 1963-; Seuss, Dr. (Universal City, CA : Universal Studios Home Entertainment, 2012)
In search of a real, live tree, a twelve-year-old boy pays a visit to the reclusive Once-ler, who tells him the story of the grumpy, yet charming Lorax, who tried to protect the forest by speaking up on behalf of the trees.
Based on the book by Dr. Seuss.
Originally released as a motion picture in 2012.
Features: additional footage, UltraViolet digital copy.
Art director, Eric Guillon ; animation director, Lionel Gallat ; editors, Ken Schretzmann, Claire Dodgson, Steven Liu ; music, John Powell.
Voices: Danny DeVito, Ed Helms, Zac Efron, Taylor Swift, Betty White.
MPAA rating: PG.
Keywords: Seuss, -- Dr. -- Film adaptations; Ecology -- Drama; Pollution -- Drama; Imaginary places -- Drama; Environmental films; Computer animation films; Fiction films; Video recordings for the hearing impaired; Based on the book; Feature films; Fantasy films; Animated films